Linking microstructure and local mechanical properties in SiC-SiC fiber composite using micromechanical testing - Zayachuk, Y; Karamched, P; Deck, C; Hosemann, P; Armstrong, DEJ (Elsevier, 2019)
Local mechanical properties of SiC-SiC fiber-reinforced composite – matrix, fiber and interphases – were evaluated using nanoindentation and microcantilever fracture testing. The fracture toughness was found to be ∼4.25 MPa*m1/2 in the matrix, ∼2 MPa*m1/2 in the fibers and ∼0.8 MPa*m1/2 at the interphases. Nanoindentation hardness was found to vary from ∼17 GPa in the center of the fibers to ∼40 GPa in the matrix. Values obtained with micromechanical testing were found to be in good agreement with the available data on bulk mechanical properties. The mechanical property variations in the different components of the composite can be explained by the variations in the microstructure. The matrix has complex hierarchical microstructure with elongated grains, often featuring twinning, growing radially from the fibers in predominantly <111> direction and forming sets of concentric rings around them. The fibers contain equiaxed grains with carbon precipitates at the grain boundaries. It was found that in the matrix fracture is transgranular, while in the fibers it can be both trans- and intergranular; at the interphases the fracture occurs at the carbon-fiber boundary. The differences in mechanical properties between the matrix and the fibers are attributed to the presence of carbon inclusions in the fibers, which reduce both hardness and fracture toughness.